Acara Halal Bihalal Sebagai Upaya Mempererat Hubungan Kekeluargaan - Muhammad Yasin; Eka Widyanti (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
Lack of family awareness to carry out Halal Bihalal is a reality that is often found in urban communities. One of the concerns of this dedication is the importance of knitting hospitality through Halal Bihalal. This dedication was carried out through collaboration between the Islamic Religious Education Study Program (PAI) and Mr. Sutarno's extended family. The implementation of this activity was carried out in Pekuncen Village, Wira Subdistrict, Village of Pekalongan Regency, the implementation of Halal Bihalal was carried out on Sundays from 08 to 12.00 WIB, namely on 5 Shawwal 1444 H or 26 April 2023. The method used is the Participatory Action Research method, where service participants are directly involved in the process of Halal Bihalal activities. The result is that community service through Halal Bihalal activities gets extraordinary enthusiasm. This can be seen from the increasing number of participating families from year to year. Another result of this service is efforts to increase family closeness through communicating regularly asking each other for news, strengthening emotional ties and connecting ties in religious events by strengthening ties through common interests and beliefs.